AMBIVALENSI KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERHADAP PROGRAM PENGEMBANGAN NUKLIR IRAN - rokhayati rokhayati (GLOBAL INSIGHT JOURNAL, 2017)
ABSTRACT Nuclear energy is an alternative source of natural resources are scarce existence. Iran is one of the countries that develop nuclear energy since 1957, but today, more and more nuclear issue has been raised internationally for the use of energy as a mass destruction weapon, Iran as a country which has nuclear development has judged violating peaceful nuclear proliferation. This research will discuss about Foreign Policy of USA which connected with Iran’s nuclear enrichment program and also about factors that influencing USA in implementing their foreign policy and what Iran does to anticipate the pressure from USA and its alliances in order to stop Iran’s nuclear program as the focus of this research. At the end, this research will try to figure out why Iran’s nuclear enrichment program got so much confrontation from USA. This research is using qualitative method with literature study technique. Key words: Nuclear Proliferation, Foreign Politics, Ahmadinejad ABSTRAK Nuklir merupakan sumber energi alternatif pengganti sumberdaya alam yang mulai langka keberadaannya. Iran merupakan salah satu negara yang mengembangkan energi nuklir sejak tahun 1957, namun dewasa ini, isu nuklir semakin diangkat di dunia internasional atas penggunaan energi tersebut sebagai senjata pemusnah massal, Iran yang sebagai negara pengembang nuklir dianggap telah melakukan pelanggaran proliferasi nuklir damai.. Tulisan  ini akan membahas mengenai kebijakan luar negeri Amerika Serikat berkenaan dengan program pengembangan nuklir Iran dan faktor-faktor apa saja yang mempengaruhi pemerintah Amerika Serikat dalam mengeluarkan kebijakan luar negerinya dan pada akhirnya tulisan ini akan mencari jawaban mengapa Program pengembangan nuklir Iran begitu ditentang oleh Amerika Serikat. Kata kunci: Proliferasi Nuklir, Politik Luar negeri, Ahmadinejad.